Alveolar type 2 epithelial cell senescence and radiation-induced pulmonary fibrosis - Zhou, Shenghui; Zhu, Jiaojiao; Zhou, Ping-Kun; Gu, Yongqing (Frontiers in Cell and Developmental Biology, 2022)
Radiation-induced pulmonary fibrosis (RIPF) is a chronic and progressive respiratory tract disease characterized by collagen deposition. The pathogenesis of RIPF is still unclear. Type 2 alveolar epithelial cells (AT2), the essential cells that maintain the structure and function of lung tissue, are crucial for developing pulmonary fibrosis. Recent studies indicate the critical role of AT2 cell senescence during the onset and progression of RIPF. In addition, clearance of senescent AT2 cells and treatment with senolytic drugs efficiently improve lung function and radiation-induced pulmonary fibrosis symptoms. These findings indicate that AT2 cell senescence has the potential to contribute significantly to the innovative treatment of fibrotic lung disorders. This review summarizes the current knowledge from basic and clinical research about the mechanism and functions of AT2 cell senescence in RIPF and points to the prospects for clinical treatment by targeting senescent AT2 cells.